2016
DOI: 10.1016/j.jacep.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Resynchronization Therapy With a Quadripolar Electrode Lead Decreases Complications at 6 Months

Abstract: The Quartet LV system significantly reduced total LV lead-related events at 6 months after implantation compared with a bipolar CRT system. The reduction in events demonstrates the superiority of this quadripolar technology to effectively manage CRT patients. (More Options Available With a Quadripolar LV Lead Provide In-Clinic Solutions to CRT Challenges [MORE-CRT]; NCT01510652).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 24 publications
4
29
0
Order By: Relevance
“…In the MORE‐CRT (More Options Available With a Quadripolar LV Lead Provide In‐Clinic Solutions to CRT Challenges) trial, 1074 patients undergoing CRT‐D were randomized in 1:2 ratio to bipolar leads or QUAD. Freedom from the composite end point of intraoperative and postoperative LV lead–related events at 6 months was greater with QUAD than with bipolar leads (83.0% versus 74.4%, P =0.0002), but this was because of differences in the intraoperative rather than postoperative events . In the present study, which involved a longer follow‐up period, QUAD was associated with a lower incidence of PNS and LV lead displacement.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…In the MORE‐CRT (More Options Available With a Quadripolar LV Lead Provide In‐Clinic Solutions to CRT Challenges) trial, 1074 patients undergoing CRT‐D were randomized in 1:2 ratio to bipolar leads or QUAD. Freedom from the composite end point of intraoperative and postoperative LV lead–related events at 6 months was greater with QUAD than with bipolar leads (83.0% versus 74.4%, P =0.0002), but this was because of differences in the intraoperative rather than postoperative events . In the present study, which involved a longer follow‐up period, QUAD was associated with a lower incidence of PNS and LV lead displacement.…”
Section: Discussionmentioning
confidence: 47%
“…Freedom from the composite end point of intraoperative and postoperative LV lead-related events at 6 months was greater with QUAD than with bipolar leads (83.0% versus 74.4%, P=0.0002), but this was because of differences in the intraoperative rather than postoperative events. 10 In the present study, which involved a longer follow-up period, QUAD was associated with a lower incidence of PNS and LV lead displacement. This might be expected in view of the fact that vector optimization almost invariably eliminates PNS in patients who initially have PNS with QUAD.…”
Section: Lead Re-interventionsmentioning
confidence: 44%
See 1 more Smart Citation
“…The randomized MORE-CRT trial [12], [13] showed an increased procedural success and reduced intra- and post-operative complications with the use of quadripolar LV leads. Contrary to the results of previous work however, our study does not show a difference in mortality or rates of hospitalizations for heart failure or PNS in recipients of quadripolar versus bipolar LV leads [11], [14], [15].…”
Section: Discussionmentioning
confidence: 99%
“…By using three-dimensional speckle tracking technique, researchers have found that multipole pacing (MPP) can reduce ventricular dyssynchrony index and increase ejection fraction [27]. A randomized controlled clinical trial has demonstrated that quadrupole electrodes can significantly reduce the perioperative complications and improve clinical outcomes [28]. However, the latest study reveals that optimization of the pacing site of a quadripolar LV lead is more important than to program MPP [29].…”
Section: Left Ventricular Electrode Implantationmentioning
confidence: 99%